Pendampingan Pembuatan Pembukuan Sederhana Pada UMKM Di Desa Sumbersari Kecamatan Moyudan Kabupaten Sleman - Diva Retafany Eriyana; Martinus Budiantara (Pusat Riset dan Inovasi Nasional, 2023)
Bookkeeping is an important aspect of business progress. In business activities, it is important to have bookkeeping to know business developments so that it can be used as evaluation material. This simple bookkeeping assistance activity was carried out for 2 MSMEs in Sumbersari Village, Moyudan District, Sleman Regency. In running their businesses, Micro, Small and Medium Enterprises (MSMEs) often find it difficult to carry out simple bookkeeping and many even do not do bookkeeping. Business people assume that if their income is sufficient to meet their daily needs, their business is profitable. The aim of the simple bookkeeping assistance provided to 2 business actors is to provide an understanding of the importance of simple bookkeeping and the ability to make simple bookkeeping so that financial bookkeeping is clearer. By having financial bookkeeping in business, business actors can find out profits or losses in the business they are running. In this activity, business actors are explained about the meaning and importance of simple bookkeeping and assistance is provided in making simple bookkeeping.